2009
DOI: 10.1073/pnas.0906652106
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vif-mediated ubiquitination/degradation of APOBEC3G involves four critical lysine residues in its C-terminal domain

Abstract: During coevolution with the host, HIV-1 developed the ability to hijack the cellular ubiquitin/proteasome degradation pathway to counteract the antiviral activity of APOBEC3G (A3G), a host cytidine deaminase that can block HIV-1 replication. Abrogation of A3G function involves the HIV-1 Vif protein, which binds A3G and serves as an adapter molecule to recruit A3G to a Cullin5-based E3 ubiquitin ligase complex. Structure-guided mutagenesis of A3G focused on the 14 most surface-exposed Lys residues allowed us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 49 publications
1
63
0
Order By: Relevance
“…Since the major function of HIV-1 Vif is to exclude A3G from HIV-1 virions, enhancement of A3G viral incorporation will have a significant impact on anti-AIDS pharmacologic strategies. Indeed, when A3G manages to be packaged into HIV-1 virions through upregulation of expression, the exosomal pathway, enhancement of packaging, or resistance to Vif-induced degradation, it can inhibit the replication of even Vif-proficient HIV-1 (1,4,13,31,33,57,68). Here, we showed that lysinedeficient A3G (A3G20K/R) was resistant to Vif-induced degradation when an HA tag was fused to the N terminus of A3G20K/R (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Since the major function of HIV-1 Vif is to exclude A3G from HIV-1 virions, enhancement of A3G viral incorporation will have a significant impact on anti-AIDS pharmacologic strategies. Indeed, when A3G manages to be packaged into HIV-1 virions through upregulation of expression, the exosomal pathway, enhancement of packaging, or resistance to Vif-induced degradation, it can inhibit the replication of even Vif-proficient HIV-1 (1,4,13,31,33,57,68). Here, we showed that lysinedeficient A3G (A3G20K/R) was resistant to Vif-induced degradation when an HA tag was fused to the N terminus of A3G20K/R (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Whether it is necessary to mutate all 20 lysines in A3G remains an open question. As briefly mentioned in the introduction, Iwatani et al showed that lysines 297, 301, 303, and 334 are critical for A3G degradation (31), as mutation of these four residues to arginines dramatically increased A3G stability. Although this observation contradicts our present data and previously published studies by us and the Zheng lab in which lysine-deficient A3G is still sensitive to Vif-induced degradation (19,60), it may be reasonable to speculate that lysines 297, 301, 303, and 334 and the N terminus of A3G are essential ubiquitin sites for Vif to induce A3G degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restriction of SIVsmm ⌬Vif was maintained upon mutation of the N-terminal A3G region but was largely lost when the C-terminal A3G domain or both deaminase domains were inactivated. These findings indicate that the C-terminal deaminase domain of A3Gsmm, much like in the human A3G, is essential for efficient lentiviral restriction (47)(48)(49)(50).…”
Section: Sivsmm Vif Efficiently Degrades Human A3gmentioning
confidence: 85%
“…In addition, viral proteins often act as adaptors, altering the specificity of E3 ligases to bring about specific protein ubiquitination, thereby hijacking the cellular Ub ligase complex (11). During HIV-1 infection, degradation of the antiretroviral factor APOBEC3G requires the association of the Vif protein with the cullin-5 ElonginB-ElonginC complex (12)(13)(14)(15)(16)(17). Vpr-mediated G 2 arrest involves the DDB1-CUL4A (VPRBP) E3 ubiquitin ligase (18)(19)(20), which is essential for viral replication.…”
mentioning
confidence: 99%